PEMETAAN KRITIK TEKS DAN KRITIK SASTRA TERHADAP KABA: SEBUAH PENELITIAN AWAL - Pramono, Pramono (Universitas Lancang Kuning, 2008)
This study is the library research by applying qualitative method. It is aimed at mapping textual and literary criticism abaout kaba. The materials for this study are all textual an literary criticism about kaba. In general, the purpose of this research is to collect the data about study of textual and literary criticism about kaba. Specifically, the purpose of this research: first, analyzing the form and the result of the result of the study of textual and literary criticism about kaba ever done; second, identifying and classifying the study of textual and literarty criticism about kaba. From the mapping of textual and literary criticism, it is found that the research on kaba is still limited compared to the number kaba existed, both orally and in the form of manuscript. Besides, for based on the research that has been done, most of them are not yet done comprehensively. Then, the research has not yet much done by the university and has not yet much been published. There fore, it seems that there are many opportunities to do the research on kaba both orally and in the form of manuscript.